Are black flies of the subgenus Wilhelmia (Diptera: Simuliidae) multiple species or a single geographical generalist? Insights from the macrogenome. (27th October 2014) - Adler, Peter H.; Inci, Abdullah; Yildirim, Alparslan; Duzlu, Onder; McCreadie, John W.; Kúdela, Matúš; Khazeni, Atefeh; Brúderová, Tatiana; Seitz, Gunther; Takaoka, Hiroyuki; Otsuka, Yasushi; Bass, Jon
<x xml:space="preserve">Abstract</x> Organisms with vast distributions often represent geographical mosaics of cryptic species. The black fly Simulium (Wilhelmia) lineatum is among the most widely distributed members of the family Simuliidae, ranging from the British Isles to eastern China. Rather than viewing S. lineatum as a possible aggregate of multiple species, taxonomists have suggested a more inclusive taxon with additional synonyms. Accordingly, S. lineatum is an ideal candidate for testing the hypothesis that a wide geographical distribution signals the presence of more than one species. A cytogenetic approach was used to probe the macrogenome of S. lineatum and other taxa proposed by taxonomists as conspecific. The banding patterns in the polytene chromosomes of 480 larvae from 15 countries across the Palearctic Region revealed 128 rearrangements of the complement. All rearrangements were autosomal and 89% were inversions nonrandomly distributed among species and among chromosome arms. The analyses clarify long‐standing confusion over previously proposed names and reveal a longitudinal succession of four species sequentially replacing one another from west to east: Simulium lineatum s.s., Simulium balcanicum, Simulium turgaicum, and Simulium takahasii. Thus, S. turgaicum is recalled from synonymy and the other three species are validated. Within the most‐represented species, S. balcanicum, the frequency of inversions follows a longitudinal gradient with a north–south bias; as the distance between the sites increases along this north‐west–south‐east axis, the similarity of inversion frequencies between sites decreases. Validation of the concept that broadly distributed black flies are composites of structurally similar species provides a framework for guiding discovery of additional biodiversity. © 2014 The Linnean Society of London, Biological Journal of the Linnean Society, 2014, 114, 163–183.